Investigating the nutrient content of food prepared in popular children's TV cooking shows. Issue 9 (24th August 2018) - Ngqangashe, Yandisa; de Backer, Charlotte; Matthys, Christophe; Hermans, Nina
Abstract : Purpose: The purpose of this paper is to analyse the nutritional content of recipes prepared in popular children's television (TV) cooking shows. Design/methodology/approach: A cross-sectional analysis of 150 recipes focusing on calorie, total fat and carbohydrates, saturated fatty acids, fibre, sugar, protein and salt content was performed. Main course recipes were evaluated against the UK Food Standards Agency (FSA), and the proportions of energy derived from each nutrient were evaluated against the World Health Organization (WHO) recommendations. Findings: While a significant proportion met the FSA and WHO recommendations for energy and salt, 58 per cent were above the FSA recommendation for total fat ( χ 2 =5.598, p =0.01), 56 per cent failed to meet the recommendations for saturated fatty acids ( χ 2 =4.551, p =0.03) and 60 per cent exceeded the FSA protein recommendations ( χ 2 =12.602, p <0.001). Only 17 and 21 per cent of the recipes met the minimum recommendations for carbohydrates ( χ 2 =30.429, p <0.001) and fibre ( χ 2 =16.909, p <0.001), respectively. Only 37 per cent had adequate portion of fruits and vegetables. The nutritional content varied depending on the composition of the recipes; vegetarian recipes were more likely to meet the recommendations than poultry, meat or fish recipes. Research limitations/implications: Foods displayed by children's popular TV cooking show fall short of the standards for healthy eating, thus warranting further research on how these shows affect eating behaviour. Originality/value: This study is the first to consider children's TV cooking shows as a platform of exposure to unhealthy foods.